Importance and benefits of farm pond construction through farmer’s participation: Success stories - Ranade, D H; Jadav, M L; Upadhyay, Ashish; Bhagat, D V; Girothia, O P (Indian Farming, 2020)
In Malwa region despite the availability of huge amount of runoff, because of satisfactory rainfall amount (average 950 mm) and vertisol area, the farmers experience shortage of irrigation water almost every year. The main reason for the same is dependency of them mainly on ground water. With the enhanced ground water availability due to sufficient rainfall, the farmers of the area cultivate rabi crops with high water demand crops i.e. wheat, onion, potato, garlic etc. simultaneously. Therefore, during December-January month the sufficient irrigation water is not available to the farmer because of lowering groundwater level. These resulted in the unsatisfactory crop production from the farmer’s point of view. Simultaneously the water that could be available from the tube well at reduced rate is also not utilized efficiently.